COVID-19, Age and Mortality: Implications for Public Policy - Whiteside, Alan; Clement, Felicia (Balsillie School of International Affairs, 2020)
The COVID-19 pandemic has paralyzed the global community, but its impacts around the world have not been homogeneous.
Keywords: Balsillie Papers; COVID-19; Public policy